Local ratcheting assessment of steel samples undergoing various step and block loading conditions. (June 2020) - Kolasangiani, K.; Varvani-Farahani, A.
Highlights: Local ratcheting of notched steel plates was examined under various loading steps and blocks. Nominal ratcheting saturated at 100 blocks and local ratcheting curve was matured in 5 blocks. The A-V/Neuber framework enabled assessing ratcheting/stress relaxation at notch root. Through finite element method, the CH model governed ratcheting progress at notch root. The choice of coefficients in the hardening rules directly influenced ratcheting response. Abstract: Ratcheting response of notched SS316 samples was examined under various loading steps and blocks. Asymmetric stress cycles following various loading blocks of Low-High-High (LHH) and High-Low-Low (HLL) sequences were applied on steel plates with notch sizes of 5, 9 and 12 mm. Local strains were measured through strain gauges mounted at the vicinity of circular notch roots. Nominal ratcheting was found to gradually progress up to a saturation limit at which ratcheting magnitude and rate stayed unchanged. Over applied cyclic loads from the first block to the 100th, local ratcheting data have shown highest rate of progress between blocks 1 and 5. Local ratcheting data at the last step of blocks 1–5 have shown an overlap reflecting a constraint induced due to evolution of plastic zone at the vicinity of notch root. The Ahmadzadeh-Varvani (A-V) kinematic hardening rule was coupled with the Neuber's rule to assess ratcheting at the notch root of steel samples. This framework enabled to predict local ratcheting over loading steps and blocks as asymmetric stress cycles were nominally applied. Local ratcheting curves predicted by the coupled framework were compared with those simulated through finite element method (FEM) through use of ABAQUS software and on the basis of Chaboche kinematic hardening model. The coupled framework showed a closer agreement with experimental data over loading steps and blocks than those simulated through FEM. Computed ratcheting curves were yet to address imbricating ratcheting curves over last steps of loading blocks in a manner similar to those of measured data.